Regional Specialization and the Supply of Wheat in the United States, 1867-1914: A Comment - Higgs, Robert (The Review of Economics and Statistics, 1971)
In a recent article in this Review, Franklin M. Fisher and Peter Temin [2] seek to illuminate the influence of regional specialization and the causes of Populism by estimating supply functions for wheat during the 1867-1914 period. Unfortunately, a fundamental error in their application of the model to the data mars the study. As a result their findings are difficult, if not impossible, to interpret, and I am skeptical that any light has in fact been shed on regional specialization or Populism. The problem arises because the variables specified by the model are different from the variables represented by the data. The model relates the share of acreage planted in wheat to the relative price of wheat, but the data are for acreage harvested in wheat. Significantly, only one price observation is available for each year: the price received by farmers on 1. Fisher and Temin recognize that the acreage planted in a given year depends upon the price in the previous year . . because farmers could not have based their decisions about planting in one year on prices of the following December [2, p. 137]. Therefore, for example, their regression explains the share of acreage harvested in wheat in 1900 as a function of its relative price in 1899 and, with geometrically declining weights, in previous years. What they overlook is that two kinds of wheat are grown: winter wheat, planted in the autumn and harvested in the late spring; and spring wheat, planted in the spring and harvested in the late summer. Within a given year, say 1900, both kinds of acreage were harvested, but while decisions concerning the acreage of spring wheat were influenced by the price on 1, 1899, and by prices in previous years, decisions concerning the acreage of winter wheat were influenced by the price on 1, 1898, and by prices in previous years. In the case of winter wheat, which constituted the bulk of the American supply during the 1867-1914 period, the acreage harvested in 1900 could not have been influenced at all by the 1899 price, since decisions concerning the planting of that acreage were made several months before the 1899 price could be observed. In states where winter wheat predominated, which include all those studied except Minnesota, Wisconsin, and the Dakotas, and possibly Iowa [6, pp. 100-101; 7], the functional form that Fisher and Temin impose on their regressions geometrically declining weights on past prices starting with the previous year is simply incapable of producing results that can be given a meaningful interpretation. The regression results obtained by Fisher and Temin might well have alerted them to potential problems. They find, for example, long-run elasticities of supply of 0.1633 for Illinois, 1.1211 for Wisconsin, and 10.7640 for Iowa. Given the great similarities of agriculture in these states, differences of this magnitude are simply incredible. Though they assert that . . the coefficients of lagged relative price were almost always 'quasi-significant' [2, p. 143], in 11 of their 34 regressions the ratio of the regression coefficient for the previous period's price to its asymptotic standard error is less than 2. And one must be uneasy about their quasi-significant coefficients in any event. Fisher and Temin offer their finding that farmers reacted slowly to a decline in the relative price of wheat as an explanation for the Populist unrest of the 1890's. Populism was hardly popular everywhere or at all times. At the very least it must be shown that the estimated reaction speeds were significantly slower in the areas of Populist strength (e.g., Kansas, Nebraska, and the Dakotas) than elsewhere, but their estimates of reaction speeds show no such systematic differences. And even if such differences were apparent, one would still be faced with the task of explaining why Populism appeared in the 1890's and not in 1903 or some other time. Recent work on Populism [1, 3, 4] has advanced considerably beyond such a casual, conjectural, and highly-aggregated approach. Quite apart from its oversight concerning winter wheat, Fisher and Temin's study suffers from a more general lack of information about agriculture during the period considered. For example, they say: If crops had declined because of poor weather, the farmer's loss of income should have been moderated by a rise in the price of crops attendant on their scarcity [2, p. 136]. But the price of wheat was established in a world market during this period, and it was common for a short crop at home to correspond with a low price, and therefore low incomes, because of bumper crops in the Ukraine, Argentina, and elsewhere in the same year [5, p. 35]. Indeed, the farmer's position as a supplier in the world market is a crucial backgrouind feature of the Populist uprising. Examples of this sort might be multiplied but the conclusion is obvious: though Fisher and Temin have focused attention on an interesting subject, the elasticities of